Coordinating knowledge hierarchies in managment: Re-conceptualising organisational wisdom - Dickie, Carolyn (Reason in Practice Limited, 2011)
This theoretical paper addresses issues associated with the hierarchical concept of the "pyramid of wisdom" to suggest that progressive organisations can implement management systems that capture and apply personal and organisational talents at various levels. A phenomenological hermeneutic approach is used to re-conceptualise components of practical wisdom in organisations. After briefly examining what constitutes Western and Eastern wisdom traditions, the paper provides various hierarchies associated with a postulated model of the pyramid of wisdom. It is argued that understanding how wisdom develops in on organisation can lead to new approaches to strategic reflection, to alternative notions of leadership, and to more holistic and democratic ways of expressing authority. Without understanding of, and practice within, the pyramid of wisdom, the personal and organisational roads to success are likely to be bleak, illusions overpowering, and accomplishments short-lived.